Epitope-Driven Vaccine Development for Zika Virus: A Bioinformatics Approach - Riska Ayu Sutriyansyah; Muhamad Hilmi Ihsanul Iman; Cahya Ajeng Valenta Tresna Sulung; Nelly Indira Kusuma Wardani; Arif Nur Muhammad Ansori (Jurnal Teknologi Laboratorium)
Zika virus (ZIKV) has become a global concern in 2015-2016, which can infect adults and developing fetuses. ZIKV is a member of the Flaviviridae family, which can spread through Aedes mosquitoes, sexual intercourse, from mother to fetus, and blood transfusions. The genetic material is single-stranded RNA with positive polarity. Conventional vaccine development requires a long time and significant resources, so the bioinformatics approach is an efficient alternative for identifying B cell epitopes as vaccine candidates. This research uses bioinformatics or In silico methods to identify B cell epitopes with the immune epitope database (IEDB) web server. This research showed that the peptide sequence of "EWFHDIPLPWHAGADTGTPHWNNKEA" (peptide 6E) in the envelope protein E of ZIKV is a potential vaccine candidate. This peptide is predicted to have high antigenicity, non-allergenicity and non-toxicity. This study concluded that peptide 6E is a promising vaccine candidate. Further studies are needed in vitro and in vivo to reconfirm that it can be used as a potential ZIKV vaccine candidate and can be applied in the future.